Ethnic Studies and the Enduring Legacy of Movements for Racial Justice in California - Centino, Nicholas (Allies for Education, 2021)
An interdisciplinary field, ethnic studies examines race, ethnicity and indigeneity with a special focus on four groups that have been historically racialized in the United States and beyond: African Americans, Asian American & Pacific Islanders, Chicanas/os & Latinas/os, and Native Americans. The historic passage of California’s Assembly Bill No. 1460 (AB1460) in 2020 calls for all incoming students across the California State University (CSU) system to complete a course in Ethnic Studies in order to graduate. For many supporters of Ethnic Studies, the signing of AB1460 into law is a long overdue recognition of the impact of Ethnic Studies to better prepare university students for a twenty first century world that still grapples with systemic racism and inequity. Rooted in the racial justice struggles of the 1960s, proponents of Ethnic Studies argue that the field’s pedagogical and epistemological tools allow for the self-representation of communities that have been historically mischaracterized and misrepresented. As such, Ethnic Studies prioritize equity and agency by its empowerment of students of all backgrounds to be voices for change.